Catch Pattern for Antarctic krill (Euphausia superba) of Different Commercial Trawls in Similar Times and Overlapping Fishing Grounds - Wang, Zhongqiu; Tang, Hao; Herrmann, Bent; Xu, Liuxiong (Frontiers in Marine Science, 2021)
Antarctic krill (Euphausia superba) is harvested using different design midwater trawls. Knowing the selective properties between trawls is crucial information for the management of the krill resources. This study compared the catch patterns between different commercial krill trawls at similar times and overlapping fishing grounds based on scientific data collected by scientific observers onboard commercial trawlers Long Teng (LT) and Fu Rong Hai (FRH). The results showed significant differences in the length-dependent catch densities and cumulative catch densities of krill between the two trawls. The krill length range in catches from LT's trawl was wider than that of FRH's trawl. Furthermore, the catch would consist of a larger proportion of smaller krill in the LT's trawl. The LT's trawl caught significantly higher proportions of krill below 38 mm than FRH's trawl. Even, the LT's trawl caught substantial numbers of krill <30 mm, whereas the FRH's trawl caught very few of them. The main factors causing the difference between trawls in catch pattern were inferred to be related to gear design including differences in mesh sizes used. The results of this study enhance the quality of comparative analysis of scientific data from commercial trawls and the understanding of gear selectivity of different configuration trawls used for harvesting krill.